Security access control system based on Radio Frequency Identification (RFID) and Arduino technologies - Ammar Faez, Mohamad Azudin (2018)
In this project, a study on the latest technologies that can be used to generate an automatic access control has been done. The aim was to create an automatic door access control system in order to solve the manual door access problem at Kolej Kediaman 2. Based on study and investigation, as mentioned in the literature review, Radio Frequency Identification (RFID) technology is chosen to be used in this proposed system based on Arduino. The RFID is an alternative technology with a potential that can replace the traditional manual door access. By using RFID technology and Arduino, the proposed system will enable students to automatically access the room using their ID card. Besides, this system also comes with warning SMS notification’s feature using GSM Modem. The advantage of the proposed system is to avoid intruders from entering owner’s room without owner’s permission. The system has been tested and show the ability to solve the manual door access control problems.